Thermal conductivity analysis of porous NiAl materials manufactured by spark plasma sintering: Experimental studies and modelling. (15th September 2022) - Nosewicz, Szymon; Jurczak, Grzegorz; Wejrzanowski, Tomasz; Ibrahim, Samih Haj; Grabias, Agnieszka; Węglewski, Witold; Kaszyca, Kamil; Rojek, Jerzy; Chmielewski, Marcin
Highlights: Effective thermal conductivity of porous NiAl samples manufactured by spark plasma sintering has been studied. Micro-CT finite element framework with additional resistance phase allows to achieve the satisfied correspondence with experimental data. Modified analytical Landauer relation with interfacial thermal resistance of necks enhances the model capability for sintered materials. Abstract: This work presents a comprehensive analysis of heat transfer and thermal conductivity of porous materials manufactured by spark plasma sintering. Intermetallic nickel aluminide (NiAl) has been selected as the representative material. Due to the complexity of the studied material, the following investigation consists of experimental, theoretical and numerical sections. The samples were manufactured in different combinations of process parameters, namely sintering temperature, time and external pressure, and next tested using the laser flash method to determine the effective thermal conductivity. Microstructural characterisation was extensively examined by use of scanning electron microscopy and micro-computed tomography (micro-CT) with a special focus on the structure of cohesive bonds (necks) formed during the sintering process. The experimental results of thermal conductivity were compared with theoretical and numerical ones. Here, a finite element framework based on micro-CT imaging was employed to analyse the macroscopic (effective thermal conductivity, geometrical and thermal tortuosity) and microscopic parameters (magnitude and deviation angle of heat fluxes, local tortuosity). The comparison of different approaches toward effective thermal conductivity evaluation revealed the necessity of consideration of additional thermal resistance related to sintered necks. As micro-CT analysis cannot determine the particle contact boundaries, a special algorithm was implemented to identify the corresponding spots in the volume of finite element samples; these are treated as the resistance phase, marked by lower thermal conductivity. Multiple simulations with varying content of the resistance phase and different values of thermal conductivity of the resistance phase have been performed, to achieve consistency with experimental data. Finally, the Landauer relation has been modified to take into account the thermal resistance of necks and their thermal conductivity, depending on sample densification. Modified theoretical and finite element models have provided updated results covering a wide range of effective thermal conductivities; thus, it was possible to reconstruct experimental results with satisfactory accuracy.